Living Law Transplantation in Construction Criminal Medical Law - Gunawan, Juliana Susanti (UIR Law Review, 2020)
Laws live and develop from patterns of behavior in society, laws are not free of values, between legality and justice are inseparable. Laws made by the authority of sovereign states that are regulated and have sanctions can work effectively if there is a relationship of moral values that provide essential justice. Medical Criminal Law (MCL) regarding medical action has not been comprehensively regulated in the legal subsystem in the health sector. The complexity of the problems that arise in society is always growing which is followed by rapid advances in medical science and technology so that MCL is needed for legal certainty for medical personnel and legal protection for the community. Literature study in normative analytical research with a conceptual approach offers the idea of moral transplantation in the construction of MCL can be built under the values that live and develop in society (living law) based on the principle of material legality